Studi Literature Review: Analisis Kualitatif Penggunaan Diksi Dalam Media Sosial Instagram - Juliana Juliana; Usiono Usiono (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The use of diction and language style used on the Instagram accounts @kumpulan_puisi and @prestigeholics, which share content about life motivation, happiness, love, and relationships, is the subject of this study. The data collected from the captions posted by the two accounts were collected through qualitative research methodology supplemented by documentation techniques. While language style was studied through the application of majas such as personification and metaphor, diction analysis focused on connotation and denotation meanings. The results showed that the use of diction in both accounts with deep and meaningful word choices reflected feelings, warnings, and advice to readers. Whether through direct comparison (metaphor) or giving human nature to inanimate objects (personification), the language style used enriches the meaning of the message to be conveyed. According to this study, diction and style play an important role in the formation of inspirational and emotional messages. They also have the ability to encourage readers to reflect on their lives and their relationships.